Microspore embryogenesis induction by mannitol and TSA results in a complex regulation of epigenetic dynamics and gene expression in bread wheat - Valero-Rubira, Isabel; Castillo, Ana María; Burrell, María Ángela; Vallés, Maria Pilar (Frontiers in Plant Science, 2023)
Reprogramming of microspores development towards embryogenesis mediated by stress treatment constitutes the basis of doubled haploid production. Recently, compounds that alter histone post-translational modifications (PTMs) have been reported to enhance microspore embryogenesis (ME), by altering histones acetylation or methylation. However, epigenetic mechanisms underlying ME induction efficiency are poorly understood. In this study, the epigenetic dynamics and the expression of genes associated with histone PTMs and ME induction were studied in two bread wheat cultivars with different ME response. Microspores isolated at 0, 3 and 5 days, treated with 0.7M mannitol (MAN) and 0.7M mannitol plus 0.4µM trichostatin A (TSA), which induced ME more efficiently, were analyzed. An additional control of gametophytic development was included. Microspores epigenetic state at the onset of ME induction was distinctive between cultivars by the ratio of H3 variants and their acetylated forms, the localization and percentage of labeled microspores with H3K9ac, H4K5ac, H4K16ac, H3K9me2 and H3K27me3, and the expression of genes related to pollen development. These results indicated that microspores of the high responding cultivar could be at a less advanced stage in pollen development. MAN and TSA resulted in a hyperacetylation of H3.2, with a greater effect of TSA. Histone PTMs were differentially affected by both treatments, with acetylation being most concerned. The effect of TSA was observed in the H4K5ac localization pattern at 3dT in the mid-low responding cultivar. Three gene networks linked to ME response were identified. TaHDT1, TaHAG2, TaYAO, TaNFD6-A, TabZIPF1 and TaAGO802-B, associated with pollen development, were down-regulated. TaHDA15, TaHAG3, TaHAM, TaYUC11D, Ta-2B-LBD16 TaMS1 and TaDRM3 constituted a network implicated in morphological changes by auxin signaling and cell wall modification up-regulated at 3dT. The last network included TaHDA18, TaHAC1, TaHAC4, TaABI5, TaATG18fD, TaSDG1a-7A and was related to ABA and ethylene hormone signaling pathways, DNA methylation and autophagy processes, reaching the highest expression at 5dT. The results indicated that TSA mainly modified the regulation of genes related to pollen and auxin signaling. This study represents a breakthrough in identifying the epigenetic dynamics and the molecular mechanisms governing ME induction efficiency, with relevance to recalcitrant wheat genotypes and other crops.